Penerapan Program Pembelajaran Muatan Lokal Sirah Nabawiyah Dalam Pembentukan Karakter Islami Di SDN Puspanegara 08 - Martina, Ary; suharmanto, fajar; Malik, Dien Nurmarina (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study investigates how the Sirah Nabawiyah learning program affects students' religious character. One of the important elements in Islamic teachings is religious character, which demonstrates a person's closeness to Allah through their daily attitudes, words, and actions. The purpose of this study is to determine: 1) This learning plan begins with needs analysis, setting learning objectives, selecting teaching methods, choosing materials, and designing activities. 2) The implementation of learning begins with classroom management, teacher-student interaction, and the use of methods and media. 3) The evaluation of this learning uses tests, assignments, observations, and portfolios. This research uses a qualitative approach with a case study type. This research was conducted at a public elementary school. Data was collected through interviews and observation and documented for interactive model data analysis. Research shows that learning more about the life of Prophet Muhammad can help people learn Islamic values such as monotheism, honesty, patience, compassion, and obedience to Allah. The study of Sirah Nabawiyah also helps strengthen students' Islamic identity and character. Therefore, learning Sirah Nabawiyah is very helpful in building a generation with noble character, high morality, and the ability to practice Islamic teachings with full awareness and responsibility. This is a strategic step towards building strong Islamic character in students.